Development of Simulink model for a microtubine system / Azlina Abdullah - Abdullah, Azlina (2009)
This thesis presents the Development of Simulink Model for a Microturbine System. The study involved the development of mathematical modeling of a microturbine system using Matlab/Simulink model. Consequently, the developed model will be evaluated in terms of electrical performances such as the voltage, current, active oiwer and reactive power of the system. Microturbine system is developed to support power distributed generation due to increasing in energy demand. It's a new way to locally supply energy facilities.